SOCIAL CLIMBING SEBAGAI AKTUALISASI DIRI KAUM MARJINAL (STUDI DESKRIPTIF DI KALANGAN REMAJA JAKARTA SELATAN) - Jaduk Gilang Pembayun (Jurnal Komunikasi dan Kajian Media, 2018)
This research was conducted to examine and analyze the ways of communicating in a "social climber" group while in their social environment at Apartments Kalibata City, South Jakarta. This study uses qualitative methods with the type of discourse analysis research. The method used by researchers is a case study with observation and interviews as a method of data collection. In the end this study aims to provide an overview and understanding of the phenomenon of "social climber" and various reasons behind it. The results of the study showed that in their interactions, the Climber group used the media to convey their messages, in the form of verbal messages and non-verbal messages. Each message is chosen according to what they want to convey to group members and their social environment by showing their roles and impressions, namely being in the middle to upper social class. they aim to be "seen" coming from the upper middle class and they can be accepted by group members and the public in their social environmentKeywords: social_climbing, descriptive, lifestyle, social status_, social acceptance.